PRODUK OLAHAN SAOS DAN PERMEN SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH PEPAYA - Mustika Wardhani, Ratna; Rekyani Puspitawati, Indah (JURNAL AGRI-TEK, 2017)
One of agricultural commodities that can be developed further as raw material of agroindustry is papaya (Carica papayaL).Papaya tree is very beneficial for health, papaya fruit is nutritious as a food digestive system, while the leaves of papaya can be made as vegetables as a traditional madicine. In Madiun Regencies most of population rely on agriculture, plantation and horticulture.although papaya is rich in nutrients but the papaya is very easily damaged, so the handling must be careful during harvesting, packaging and transportation. Therefore processing papaya into various processed products is the right solution to overcome the problem, in additional to increase the added value. In order to increase the added value of papaya, papaya fruit processed as a papaya candy and papaya sauce. Based on the problem above, the purpose of research to be achieved is to analyze the added value of papaya commodities into processed products as a candy and papaya sauce. From the research that has been done can be concluded as follows: (1) The added value created from each kilogram of fresh papaya into papaya sauce is IDR 5.919,9 or 65.7% of production cost. (2) The added value created from each kilogram of fresh papaya into papaya candy is IDR 4.100,0 or 54.6% of production cost. Keywords: Added Value, Processed Product, Papaya